2003
DOI: 10.1289/ehp.5778
|View full text |Cite
|
Sign up to set email alerts
|

The role of transgenic mouse models in carcinogen identification.

Abstract: In this article, we examine existing data on the use of transgenic mouse models for identification of human carcinogens. We focus on the three most extensively studied of these mice, Trp53+/-, Tg/AC, and RasH2, and compare their performance with the traditional 2-year rodent bioassay. Data on 99 chemicals were evaluated. Using the International Agency for Research on Cancer/Report on Carcinogens determinations for the carcinogenicity of these chemicals to humans as the standard for comparison, we evaluated a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 74 publications
2
102
0
Order By: Relevance
“…With the ILSI initiative and individual lab testing, a wide variety of chemicals have been tested on Tg.AC mice in an effort to validate the model Spalding et al, 1999Spalding et al, , 2000. An extensive analysis of those chemical tests has recently been performed (reviewed in Pritchard et al, 2003;Sistare et al, 2002) and a compilation of tests and references can be found on the Tg.AC website at http://dir.niehs.nih.gov/dirlecm/TgAC/TgAC_Home.htm. The data from these studies show that a variety of chemical carcinogens can generate a tumorigenic response in Tg.AC mice, including both genotoxic and nongenotoxic carcinogens.…”
Section: Tgac and Chemical Carcinogenesismentioning
confidence: 99%
“…With the ILSI initiative and individual lab testing, a wide variety of chemicals have been tested on Tg.AC mice in an effort to validate the model Spalding et al, 1999Spalding et al, , 2000. An extensive analysis of those chemical tests has recently been performed (reviewed in Pritchard et al, 2003;Sistare et al, 2002) and a compilation of tests and references can be found on the Tg.AC website at http://dir.niehs.nih.gov/dirlecm/TgAC/TgAC_Home.htm. The data from these studies show that a variety of chemical carcinogens can generate a tumorigenic response in Tg.AC mice, including both genotoxic and nongenotoxic carcinogens.…”
Section: Tgac and Chemical Carcinogenesismentioning
confidence: 99%
“…Here, we adopted a short-term bioassay, i.e., the p53 heterozygous mouse intraperitoneal exposure model reported to be sensitive to asbestos and develop mesotheliomas fast (Marsella et al, 1997;Vaslet et al, 2002). This mouse model has been reported to be sensitive not only to genotoxic carcinogens (Pritchard et al, 2003) but also to reactive oxygen species (ROS)-related carcinogenesis (Tazawa et al, 2007) and therefore fits with the postulated carcinogenesis mechanisms of asbestos and asbestos-like particles (Marsella et al, 1997;Vaslet et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The Tg.AC mouse has been proposed to be a good predictor of human carcinogens applied topically and responds with sensitivity to both mutagenic and nonmutagenic carcinogens (Spalding et al, 1993;Pritchard et al, 2003). However, the sensitivity of this model to wounding and chronic irritation may also be its greatest weakness.…”
Section: Discussionmentioning
confidence: 99%